Estuarine Circulation, Mixing, and Residence Times in the Salish Sea. Issue 2 (10th February 2021) - MacCready, P.; McCabe, R. M.; Siedlecki, S. A.; Lorenz, M.; Giddings, S. N.; Bos, J.; Albertson, S.; Banas, N. S.; Garnier, S.
Abstract: A realistic numerical model is used to study the circulation and mixing of the Salish Sea, a large, complex estuarine system on the United States and Canadian west coast. The Salish Sea is biologically productive and supports many important fisheries but is threatened by recurrent hypoxia and ocean acidification, so a clear understanding of its circulation patterns and residence times is of value. The estuarine exchange flow is quantified at 39 sections over 3 years (2017–2019) using the Total Exchange Flow method. Vertical mixing in the 37 segments between sections is quantified as opposing vertical transports: the efflux and reflux. Efflux refers to the rate at which deep, landward‐flowing water is mixed up to become part of the shallow, seaward‐flowing layer. Similarly, reflux refers to the rate at which upper layer water is mixed down to form part of the landward inflow. These horizontal and vertical transports are used to create a box model to explore residence times in a number of different sub‐volumes, seasons, and years. Residence times from the box model are generally found to be longer than those based on simpler calculations of flushing time. The longer residence times are partly due to reflux, and partly due to incomplete tracer homogenization in sub‐volumes. The methods presented here are broadly applicable to other estuaries. Plain Language Summary: The Salish Sea is a large estuarine system that includes the cities of Vancouver on the Strait of Georgia and Seattle on Puget Sound. Despite the many rivers flowing into the Salish Sea, the water in the system is mostly ocean water, and there is rapid exchange with the ocean. This exchange is important because it brings in most of the nutrients that feed the ecosystem, and it flushes the system relatively rapidly, leading to generally good water quality. Nonetheless, there are places and times in the Salish Sea that experience problems like hypoxia and fish kills. The goal of this work is to clearly describe the patterns of circulation and mixing throughout the Salish Sea so that we may understand the causes and potential future changes in these water quality problems. We use a realistic computer simulation, tested against many observations, to predict the circulation and mixing patterns. We then use those currents to estimate residence times in different parts of the Salish Sea for different seasons and years. The most important result is that we find that the mixing of surface water with deep water can distribute water properties throughout the Salish Sea, increasing the residence time. Key Points: The estuarine circulation throughout the Salish Sea is estimated over 3 years from a realistic numerical model, focusing on the exchange flow The vertical mixing, or "reflux" is stronger at sills, but is also large when integrated over the basins between sills Residence time is calculated in three ways, quantifying the extent to which it is increased (often more than doubled) by reflux and incomplete homogenization within a volume